2015
DOI: 10.1016/j.landurbplan.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

What accounts for ‘England's green and pleasant land’? A panel data analysis of mental health and land cover types in rural England

Abstract: Exposure to green space is associated with a variety of positive health states. Research to date has focused primarily on 'generic' green space in urban areas, where green space is relatively scarce and where it is dominated by playing fields and parks. The current research adds to our understanding with an examination of relationships between different types of green space and mental health in rural areas in England (approximate rural population = 4 million). The aggregate land cover classes of Land Cover Map… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 46 publications
5
78
0
3
Order By: Relevance
“…However, it is consistent with findings of associations between coastal environments and mental health specifically within rural areas of the UK (Alcock et al, 2015). White et al (2014) showed a strong proximity gradient for physically active coastal visits in England among adults (see also Elliott et al, 2015) and a similar possibility could be hypothesised for children.…”
Section: Discussionsupporting
confidence: 84%
“…However, it is consistent with findings of associations between coastal environments and mental health specifically within rural areas of the UK (Alcock et al, 2015). White et al (2014) showed a strong proximity gradient for physically active coastal visits in England among adults (see also Elliott et al, 2015) and a similar possibility could be hypothesised for children.…”
Section: Discussionsupporting
confidence: 84%
“…This paper empirically identifies several pathways and mediators for the linkage of public health to land use. Our findings confirm the hypothesis that green land has complex mechanistic links with public health as people use green spaces for a wide spectrum of purposes (Alcock et al, 2015). Three pathways are generated and they demonstrate that green land can impact public health through purifying air, increasing physical activity, and promoting social interactions.…”
Section: Public Health In Linkage To Land Usesupporting
confidence: 84%
“…Some cases move from the urban areas to the rural places. A panel data analysis demonstrates that good mental health is positively related to natural spaces in rural England (Alcock et al, 2015). Almberg et al (2014) reports that adverse birth outcomes (preterm births and low birth weight) are significantly positive related to agricultural land use for rice and cotton.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, research in this area has demonstrated that living within a neighbourhood with more generic 'greenspace' (e.g., as measured using satellite images) is associated with a lower risk of common mental health problems such as anxiety and depression [13,[95][96][97][98][99]. The focus has been in exploring the following areas: (a) different types of greenspace in urban areas (e.g., street trees [10,100]; (b) greenspace land cover in rural areas (e.g., managed grasslands, deciduous woodlands, moorland, [101]); and (c) well-being outcomes in relation to different exposure types (e.g., evaluative, eudaimonic (i.e., feelings of meaning and achievement), and experiential well-being [102]). In Theme 2 of the HPRU, we have also quantified the effects of urban infrastructure on local urban temperatures compared the potential co-benefits with temperatures in green environments and quantified the related health impacts [103], as well as the impact of factors such as the deprivation status of people in relation to exposure to the highest urban temperatures [104].…”
Section: Benefits Of Natural Environmentsmentioning
confidence: 99%